Urinary exosomal microRNA profiling in intermediate-risk prostate cancer - Mee Young Kim (Nature Portfolio, 2021)
Abstract MicroRNAs (miRNAs) of urine exosomes have emerged as biomarkers for urological cancers, owing to their high stability. MiRNAs have been linked to factors associated with aggressive prostate cancer such as biochemical recurrence (BCR) and metastasis. In this study, we aimed to identify urinary exosomal miRNAs as prognostic markers associated with BCR in intermediate-risk prostate cancer. We profiled the expression levels of miRNAs via next generation sequencing in urinary exosomes from 21 non-BCR patients and 6 BCR patients of intermediate-risk prostate cancer. A total of 21 urinary exosomal miRNAs were found to be differentially expressed (> twofold) in BCR patients compared to non-BCR patients. For external validation, we validated these results using quantitative reverse transcription PCR in an independent cohort of 28 non-BCR patients and 26 BCR patients. A validation analysis revealed that three miRNAs (miR-26a-5p, miR-532-5p, and miR-99b-3p) were upregulated in exosomes from BCR patients. The univariate and multivariate Cox regression analyses showed that miR-532-5p was an important predictive factor for BCR of intermediate-risk prostate cancer. In conclusion, miR-532-5p in urine exosomes might be a potential biomarker for predicting BCR, which is a poor prognosis in patients with intermediate-risk prostate cancer. Further research is needed on the biological functions and mechanisms of this miRNA.